PENYUSUNAN RENCANA KERJA MADRASAH DI MADRASAH ALIYAH NEGERI 1 PEKANBARU - Nurhasimah Nurhasimah; Nunu Mahnun; Rini Setyaningsih (stit-islamic-village, 2020)
The aim of this research was to investigate the arrangement of the madrasa work plan in Madrasah Aliyah 1 Pekanbaru. The type of this research was descriptive qualitative research, the subject of this research was the headmaster, the head of administration, the vice headmaster of the curriculum, the student affairs, and facilities and infrastructure. The object of the research was the arrangement of the madrasa work plan in Madrasah Aliyah 1 Pekanbaru. The techniques used in collecting data were interview and documentation. The analysis method used transcribing, coding, categorizing, and interpreting data. The research finding was the headmaster had designed the madrasa work plan by 1) Forming work plan by involving the head of administration, the vice headmasters, and school committee; 2) Giving direction about arranging madrasa work plan such as basics of arrangement, objectives, and budget needed in arranging madrasa work plan; 3) Arranging plan of activities such as description of activities, implementation, and expected results; 4) Arranging draft of RKJM by identifying real challenge and making work program; 5) reviewing and revising draft of RKJM; 6) Finalizing revision result of RKJM by executing the approval; 7) Signing the result of RKJM as Madrasa Strategic Plan; 8) arranging draft of RKT; 9) Reviewing and revising draft of RKT, and 10) Finalizing revision result of RKT by executing the approval. 11)Signing the result finalization of RKT as Madrasa Annual Activity Plan and Budget.